Mummy, me and her podcast: Family and gender discourses in contemporary podcast culture: Not by Accident as audio(auto) biography. (1st June 2019) - Zehelein, Eva-Sabine
Podcasts can perform transdisciplinary cultural work in sonic form. Often, they are specific 'soundworks' which, though still emphasizing speech and words over sound and noise, still challenge the predominance of text and image by necessitating the 'social act' of listening. Not by Accident, 'a documentary series about choosing to become a single mother and coping with being one' (Harper), presents an example of how private and intimate stories, told to an (anonymous) audience can function as both scriptotherapy, and oral/aural (auto)biographical texts (here of mother and daughter), but also as self-help and awareness raising narratives for a community of listeners, a sound-based social network. By illustrating the private impact of public family policies and social discourses, Harper's podcast speaks against discrimination and denigration of single mothers, lesbian mothers and single mothers by choice, against patriarchal motherhood and the heteronormative model of the 'nuclear family' and for reproductive justice in families of choice.